Evaluation of Pedestrian's Profile, Activity, and Environment in the City of Kitakyushu, Japan - Fritz Akhmad Nuzir (Journal of Science and Applicative Technology, 2018)
Various attributes addressing the issues on walking environment and walking condition possibly has distracted the efforts of creating better planning and development to promote walking to the citizen. It will take an enormous effort and time for them to consider all the attributes that are available. Therefore authors assess the possibilities of the utilization of the Pedestrian PL.AC.E. (Profile, Activity, and Environment) and its key-attributes using a survey questionnaire in order to confirm that it can serve as a framework for urban planning or assessment in promoting a walking-friendly environment. The questionnaire was distributed to the case study area which is the city of Kitakyushu, Japan. After collecting and documenting all responses, the results were analyzed using descriptive type of statistical analysis with SPSS software.